An Efficient Method of Preparation and Comprehensive Properties for Energetic Salts Based on Nitrofurazan‐Functionalized Hydroxytetrazoles. Issue 42 (12th November 2018) - Guo, Tao; Wang, Zijun; Huo, Huan; Tang, Wang; Zhu, Yong; Bi, Fuqiang; Wang, Bozhou; Meng, Zihui; Prof. Zhongxue Ge, and
Abstract: Based on the advantages of the furazan and tetrazole ring, the nitro and N‐oxide groups were introduced into furazan‐tetrazole backbone to four kinds of novel nitrofurazan‐functionalized hydroxytetrazole energetic salts. Various method have been employed to confirm their structures, such as multinuclear NMR, FTIR spectroscopy and elemental analysis. Salt guanidinium 5‐(4‐nitro‐furazan‐3‐yl)‐tetrazole‐1‐olate (5 ) and salt potassium 5‐(4‐hydroxyamino‐furazan‐3‐yl)‐tetrazole‐1‐olate (6 ) has been further elucidated by single‐crystal X‐ray diffraction. The non‐isothermal decomposition kinetics and thermodynamics for different salts were investigated by using TG‐DSC with different heating rate. The physico‐chemical properties and detonation performance were also studied and calculated by EXPLO5 program, in which salt hydroxylammonium 5‐(4‐nitro‐furazan‐3‐yl)‐tetrazole‐1‐olate (3 ) have a relatively high density of 1.839 g⋅cm −3 at 296 K and good detonation properties ( v D = 9228 m⋅s ‐1, P = 38.0 GPa), which is superior to that of RDX. The sensitivities towards impact and friction were also determined by BAM method (BAM Fallhammer Test for IS; BAM Friction Test for FS), in which the salt 5 showed very insensitive property (IS>60 J, FS>360 N) and can be comparable to that of TATB. Furthermore, the specific impulse of salt 3 (281 s) was even better than that of ammonium perchlorate (AP) (157 s) as neat compounds. Abstract : The nitro group and N‐oxide groups were introduced into furazan‐tetrazole backbone to synthesize a series of novel nitrofurazan‐functionalized hydroxytetrazole energetic salts, where salt 3 exhibited a good detonation performance and moderate sensitivity.